PENGARUH NPL,LDR DAN NIM TERHADAP ROE PADA BANK BJB PERIODE TAHUN 2007 - 2024 - Jumiati, Jumiati; Jelita, Anggun; Aurelia Hamzah, Chika; Yemima Christy, Ulina; Florentina Seno, Maria; Sumantri, Fazhar (Kajian Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR),and Net Interest Margin (NIM) on Return on Equity (ROE) at Bank BJB during the period 2007 to2024. The method used in this study is a descriptive quantitative approach using secondary dataanalyzed through multiple linear regression. The results of the study indicate that NPL and LDR donot have a significant effect on ROE partially, while NIM has a positive and significant effect onROE. Simultaneously, the three independent variables (NPL, LDR, and NIM) have a significanteffect on ROE. This finding confirms the importance of interest income efficiency in increasing bankprofitability.